Effects of Bending and Re-bending on Mechanical Properties of Locally-Manufactured Steel Rebars - Waruhiu, Patrick W.; Marandu, Simon I.; Mgwatu, Mussa I. (Tanzania Journal of Science, 2024)
Steel rebars experience deformation when subjected to bending and re-bending operations. Subsequently, their microstructures are impaired thus affecting the mechanical properties and leading to failure. This study establishes the effects of bending and re-bending the steel rebars on the mechanical properties. Experiments were conducted to determine the effects of bending and re-bending of the steel rebars. Testing was conducted on Ten virgin and Thirty specimens which were bent and re-bent at 45º, 90º, and 180º, and followed by tensile tests. Yield strength, ultimate tensile strength, elongation, and ultimate tensile strength to yield strength ratio (Rm/Re), were recorded. Results showed the yield strength, ultimate tensile strength, elongation, and Rm/Re of virgin steel rebars varied from 553.62 MPa to 618.49 MPa, 634.39 MPa to 745.68 MPa, 17.6 % to 21.67 %, and 1.14 to 1.19. The yield strength, ultimate tensile strength, elongation, and Rm / Re of bent and re-bent steel rebars at angles of 45º, 90º, and 180º varied from 603.67 MPa to 677.38 MPa, 692.82 MPa to 751.76 MPa, 6.88 % to 19 % and 1.09 to 1.21. It was established that bending and re-bending increase strength and reduce the ductility of the rebars proportionally.